Pendidikan Dinamika Demokrasi dalam Peristiwa Suksesi di Saqifah Bani Saidah dan Peralihan Kepemimpinan Khulafa’ Ar-Rasyidin - Hafizh Syah Reza Pahlevi; Nasihun Amin (Universitas Muhammadiyah Makassar, 2021)
The beginning of the internal conflict of Muslims in political affairs began after the death of the Prophet Muhammad, where the people faced disputes when they wanted to determine the leader of Muslims as the succession of leadership from the Prophet Muhammad. The Ansar and the Muhajirin both felt worthy and entitled to be the successors of the Prophet Muhammad, they gathered at Saqifah Bani Saidah to discuss the issue. The purpose of this study is to reveal some historical facts that existed in the Saqifah Bani Saidah incident and the transition of leadership during the Khulafa'Ar-Rasyidin period so that they can be used as educational and teaching materials regarding the dynamics of democracy. The method of this research is a library research. The results of this study are the events in Saqifah became a step that marked the birth of Rashidun with Abu Bakr's position as the first caliph for Muslims who were democratically elected based on the agreement of the majority of the people in that place. The transition of leadership during the Khulafa' Ar-Rasyidin period was not hereditary in one line of leadership. The conclusions of the events in Saqifah Bani Saidah listed in this paper are; (1) The event in Saqifah became a discussion forum for modern democratic politics, with the agreement of the majority of the local community to vote for Abu Bakr. (2) The model of government in the era of Khulafa' Ar-Rasyidin tends to be a republican model. (3) The events in Saqifah Bani Saidah resulted in a political resolution to the political development and the Islamic state administration system.